PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA PROGRAM AKSELERASI - Bahruddin Zaini (stit-islamic-village, 2020)
The researcher aims to analyze the implementation of Islamic religious education learning in the acceleration program at SD State University Laboratory Malang which includes PAI learning planning in the accelerated program at SD LAB UM, the implementation of PAI learning in the acceleration program at SD LAB UM, and the evaluation of PAI learning in the acceleration program at UM LAB SD. Researchers use a qualitative approach, while the type of research uses case studies. The results of this study are the implementation of Islamic Education Learning in the acceleration program at SD Laboratory State University of Malang, Includes: First the planning of PAI learning in the acceleration program at SD LAB, there are three stages in this planning. implemented by P2LP. The second stage of preparation in which all teachers must be able to compile and make their own learning models. The third stage of development where the teacher must be able to develop learning devices. The implementation of PAI learning in the acceleration program in SD LAB starts from the selection of learning models. While the evaluation in the acceleration program is carried out continuously and continuously to obtain information about the progress and success of student learning.